The Influence of Compensation, Work Environment, and Career Development on the Turnover Intention of Mitra Mandiri Kabanjahe Cooperative Employees - Nursanti, Emmy; Marpaung, Nicholas (PT FORMOSA CENDEKIA GLOBAL, 2024)
Increasing productivity and organizational stability is highly dependent on employee satisfaction and loyalty. In this context, this research specifically focuses on understanding the impact of compensation, work environment, and career development on employee motivation which is very significant. to resign, collectively known as turnover intention. The method used is a quantitative method. Research will be conducted with a sample of 30 respondents. The research results show that there is a partial and significant influence between the compensation, work environment and career development variables on the turnover intention variable, and there is a simultaneous and significant influence of each independent variable on the dependent variable. Based on the results of the data analysis carried out, it can be concluded that the compensation, work environment and career development variables have a significant impact with negative values or in the opposite direction to the turnover intention variable